Orchestrating frugal eco-innovation: the plethora of challenges and diagnostics in lean startups of emerging economies (INMR - Innovation & Management Review, 2023)
Purpose – Sustainable development research assumes that startups, under extreme financial constraints, cannot sacrifice resources now for benefits later without risking their survival. Furthermore, their non-compliance with environmental regulations adds fuel to the fire. This paper aims to explore the challenges faced by startups in resource-scarce economies and the innovative ways of coping with these challenges. Design/methodology/approach – The data for the study was collected through 17 semi-structured interviews taken from startup owners and industry experts based in Pakistan and Bangladesh. The transcribed data were coded through NVivo 12 and themes were generated by merging 47 open and 14 axial codes. Findings – The findings show that a lack of government support and lack of organisational readiness and motivation significantly affect startups’ frugal eco-innovation. Empirical evidence reveals problems related to the business ecosystem, and internal organisational issues also contribute to challenges faced by startups in attaining a competitive position in the industry. Research limitations/implications – The study’s findings suggested leveraging dynamic capabilities can help lean startups in frugal eco-innovation. Furthermore, organisational cohesion, business ecosystem, government regulations and assistantship, organisational mismanagement and market realisation are decisive in startups’ competitive position in emerging economies. Practical implications – The findings of the study will result in a higher adoption rate of more competitive business models, and hence, startups’ sustainability. The results would be an effective and efficient deployment of sustainable technological solutions, creating more customer and shareholder value leading to economic growth. Originality/value – This research offers a comprehensive analysis of frugal eco-innovative startups by exploring the interplay between different challenges and organisational capabilities. Furthermore, the study contributes to the existing body of knowledge by providing empirical evidence that ecoinnovation can be conducted in a resource-constrained environment. This study challenged the scholarly and managerial assumption of the availability of finances as a significant player in eco-innovation. The study also links the Darwin theory of startups to a competitive edge over rivals for startups’ survival.